"What makes it worth the investment to say it?" – Care experiences of lesbian, gay, bisexual and/or trans* people facing life-limiting illness: a qualitative interview study. Issue 3 (1st September 2016) - Bristowe, Katherine; Hodson, Matthew; Wee, Bee; Almack, Kathryn; Daveson, Barbara; Koffman, Jonathan; McEnhill, Linda; Johnson, Katherine; Harding, Richard
Abstract : Introduction: People who identify as lesbian, gay, bisexual and/or trans* (LGBT) have increased risk of certain life-limiting illnesses. Evidence suggests they may not receive the care and support they need towards the end of life and into bereavement. 1, 2 Aim: To inform training and resources to improve care, this original study aimed to explore care experiences of LGBT people facing life-limiting illness, by eliciting experiences of: sharing identity (sexual identity/gender history) in healthcare settings; accessing services; discrimination/exclusion; and examples of good practice. Methods: In-depth qualitative interview study. Participants were recruited across the UK (England, Wales, Scotland) via clinical teams, social media and community networks. Interviews were transcribed verbatim and analysed using thematic analysis. Results: 40 LGBT people were interviewed: 20 patients, 6 informal carers, 14 bereaved informal carers; 21 described cancer experiences, 16 non-cancer, 3 co-morbid cancer/non-cancer; and mean age was 60 (range 27–94). Five main themes emerged: 1) palliative care needs that may require additional or different consideration for LGBT people; 2) communicative or service level barriers and stressors, including heteronormative assumptions, and homophobic/transphobic behaviours; 3) internalised or invisible barriers and stressors, including fears, or experiences, of discrimination, 4) which shape individuals' preferences for disclosure and exploration of identity; and 5) communicative or service level facilitators to accessing care and support. Conclusions: Despite recent legislative change for LGBT people, experiences of discrimination and exclusion in advanced disease and palliative care are still evident. A resource, co-designed with the LGBT community, is being piloted, and learning events being delivered nationally. References: Harding R, Epiphaniou E, Chidgey-Clark J. Needs, experiences and preferences of sexual minorities for end-of-life care and palliative care: a systematic review. J Palliat Med 2012;15 :602–611 Bristowe K, Marshall S, Harding R. The bereavement experiences of lesbian, gay, bisexual and/or trans* people who have lost a partner: a systematic review, thematic synthesis and modelling of the literature. Palliat Med 2016